Factors associated with progression of different prediabetic status to Diabetes: A Community-based cohort study. (February 2022) - Li, Na; Lu, Chunhua; Ma, Yuhang; Wang, Xuejiao; Ling, Yunxia; Yin, Yanhua; Li, Shumei; Huang, Jiao; Yu, Lihua; Dong, Weiping; He, Huichen; Kang, Mei; et al.
Abstract: Aims: To examine the predictive factors associated with the progression of different prediabetic status to diabetes. Methods: A two-year retrospective cohort study was conducted on 5741 participants aged 40 years or older. Finally, 1685 participants with prediabetes defined by IFG (impaired fasting glucose), IGT (impaired glucose tolerance) and CGI (combined IFG and IGT) were included. Logistic regression model was used to evaluate the risk of prediabetes progression to diabetes. Results: Of the 1685 subjects with prediabetes at baseline, 212 (12.6%) subjects progressed to diabetes and 1473 (87.4%) subjects did not. Logistic regression analysis demonstrated that people with CGI were associated with an increased risk of progressing to diabetes compared to those with IFG (OR, 95% CI: 3.127, 2.047–4.776). Moreover, males, obese people, people with increased BMI and WHR (Waist/ Hip ratio), and hypertension were positively associated with the progression to diabetes, while HOMA-β was negatively associated with the progression to diabetes. Conclusions: Subjects with CGI are prone to progressed to diabetes compared to those with IFG or IGT in middle-aged and older person in China. More attention should be paid to male and obese prediabetic subjects, and measures should be taken to control the increase in their BMI and WHR.